The First Element of Command Responsibility - The Existence of the Relationship of Superior - Subordinate In the International Customary Law - Ćosić Dedović, Jasmina; Idrizović , Sedin (Kriminalističke teme, 2021)
Proper understanding of the constitutive elements of the command responsibility is the key to its proper application in practice, and the relationship between superior and subordinate as well as effective control is certainly one of the more complex issues that is insufficiently elaborated in the professional public and the public at large. The constitutive elements of the superior’s command responsibility have their roots in the customary international law. One of these elements, without which there is no command responsibility of the superior, is the existence of a superior-subordinate relationship, which at its core implies existence of the effective control of the superior over the subordinate. The ad hoc tribunals of the former Yugoslavia and Rwanda paid particular attention to interpretation of this element of command responsibility in their jurisprudence. The goal of the authors is to show the context in which this first element of command responsibility gained "its place" in the international customary law and international conventional law as well as to show how the first element has been interpreted in jurisprudence. Therefore, in the context of this first element, the paper deals with the analysis of customary international law, international agreements and individual decisions of international ad hoc tribunals.